Tracking King Tiger : Reies López Tijerina and the FBI - Gutierrez, Jose Angel (Book collections on Project MUSE., 2019)
"This book explores the life of Reies Lopez Tijerina, with a particular focus on the FBI's treatment of him and his family"--